Optimalisasi Potensi Desa Haurkuning untuk Peningkatan Ekonomi Masyarakat Melalui Pemanfaatan Limbah Padi dan Penguatan UMKM: Pengabdian - Kevina Zelia Putri; Muadzin Nur Mubarok; Meisya Putri Syahrani; Jelita Septiani; Nazwa Zahra Fakhira Santosa; Anisa Maulida; Zakqi Ramadhan; Naila Salsabila; Rifka Aulia Johar; Imam Amin Tohirin; Riyanda Utari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) in Haurkuning Village, Paseh District, Sumedang Regency, was implemented to optimize local potential through the utilization of rice waste and the strengthening of Micro, Small, and Medium Enterprises (MSMEs). This community service activity focused on training and socialization on the utilization of rice husks into economically valuable charcoal, as well as assisting MSMEs in product packaging and marketing. The methods used included physical interventions in the form of demonstrations on how to make charcoal from rice husks and non-physical interventions in the form of education and discussions with farmer groups. The results of the activity showed an increase in the capacity and knowledge of farmers in managing rice waste, a reduction in environmental pollution, and the emergence of economic added value through marketable rice husk charcoal products. In addition, this activity encouraged the strengthening of village MSMEs in increasing the competitiveness of local products. Overall, the KKN program in Haurkuning Village made a real contribution to community empowerment based on local potential oriented towards economic, social, and environmental sustainability.